Challenges and Strategies for Controlling Indonesia's Emerging and Re-Emerging Infection Diseases (EID-REIDs) - Erwin Astha Triyono; Merita Arini; Tri Pudy Asmarawati; Hendy Wirantara; Feriawan Tan (Acta Medica Indonesiana)
This review aims to highlight the occurrences of several emerging and re-emerging infectious diseases, particularly 13 types under surveillance of Indonesia’s emerging contagious disease task force. These diseases are considered potentially epidemic, due to the nature of tropical climate and high humidity of Indonesia’s area. Several factors contribute to the emergence of these diseases: in conjunction with human behavior. Most of these diseases are zoonotic, specifically spread by viruses. The latest emerging infectious disease in Indonesia is monkeypox. Controlling the management of EID-REIDs presents a major obstacle for international health initiatives, particularly in Indonesia because of its extensive population, varied geographical landscape, and constrained resources. Overcoming these obstacles demands tactics like prioritizing Indonesian policies, bolstering disease monitoring systems, upgrading diagnostic capacities, fortifying public health facilities, fostering community involvement and education, and executing efficient prevention and management protocols. These strategies should be implemented in collaboration with international partners and organizations to effectively control and prevent the spread of emerging and re-emerging infectious diseases in Indonesia.